Elevated Serum C-Reactive Protein and Markers of Sleep Disordered Breathing. (19th February 2012) - Wiener, R. Constance; Zhang, Rouxin; Shankar, Anoop
Abstract : Background . Previous studies indicated sleep-disordered breathing (SDB) is associated with cardiovascular disease (CVD). Systemic inflammation is recognized as a risk factor for CVD. Studies examining SDB and inflammation are limited. Methods . We studied sleep duration, snoring, snorting, and daytime sleepiness, and an additive SDB score. The main outcome was a C-reactive protein (CRP) of >1 mg/dL. Results . Snoring, snorting, daytime sleepiness, and sleeping >7 or <7 hours, and the additive score were significantly associated with high CRP. The additive score was not associated in men but moderately associated in women in a multivariable model adjusting for age, gender, race/ethnicity, education, smoking, hypertension, alcohol intake, physical activity, body mass index, depression, diabetes, hypertension, and total cholesterol ( P -interaction = 0.42 ). For race/ethnicity, the association was strongest in Mexican Americans/others, modest in Non-Hispanic whites, and absent in Non-Hispanic blacks ( P -interaction = 0.07 ). Conclusions . The association between SDB and high CRP was present mainly in women and Mexican Americans, implying SDB has a residual, independent association with inflammation after controlling for lifestyle and metabolic risk factors like BMI, physical activity, depression, diabetes, and cholesterol.